Optimization of Breast Milk Production with Breastfeeding - Siti Farida; Noor Arniwati Mat Daud; Ropitasari Ropitasari (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Optimal breastfeeding practices are the key to reducing stunting in children under the age of five. Breastfeeding mothers in carrying out their roles are often faced with various challenges. Lack of confidence in breastfeeding mothers can affect breast production. Hypnobreastfeeding is a natural method of using subconscious energy so that the breastfeeding process runs comfortably, smoothly and can produce sufficient milk for the needs of the baby's growth and development. Objective : Determine the effectiveness of hypnobreastfeeding on breast milk production. Method : This type of research is Pre experimental Design with One Group Pretest-Postest Design, namely by comparing 1 group with 2 treatment namely observing the volume of breast milk in nursing mothers before and after being given hypnobreastfeeding. The sample in this study were 20 breastfeeding mothers who met the inclusion criteria. Results : The results of the statistical test obtained a p-value of 0.000 so that it can be concluded that hypnobreastfeeding is effective for overcoming the problem of breast milk production in breastfeeding mothers. Conclusions : There is a significant effect between hypnobreastfeeding on breast milk production. The volume of breast milk in breastfeeding mothers increases after hypnobreastfeeding 2 times a day for 3 days. For health care providers, hypnobreastfeeding can be applied to postpartum mothers as a method of lactation management to prepare mothers physically and mentally to be able to breastfeed and believe that breast milk production is sufficient according to baby needs.